1992
DOI: 10.1007/bf00235074
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium mediated transfer of a mutant Arabidopsis acetolactate synthase gene confers resistance to chlorsulfuron in chicory (Cichorium intybus L.)

Abstract: Leaf discs of C. intybus were inoculated with an Agrobacterium tumefaciens strain harboring a neomycin phosphotransferase (neo) gene for kanamycin resistance and a mutant acetolactate synthase gene (csr1-1) from Arabidopsis thaliana conferring resistance to sulfonylurea herbicides. A regeneration medium was optimized which permitted an efficient shoot regeneration from leaf discs. Transgenic shoots were selected on rooting medium containing 100 mg/l kanamycin sulfate. Integration of the csr1-1 gene into genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The combinations of NAA with either KIN or BAP produced similar results while the combination of IAA with KIN was significantly more successful than that with BAP in terms of the mean number of shoots produced per explant (18.3 shoots vs. 10.7 shoots, respectively). This finding is consistent with the results of Vermeulen et al (1992) who demonstrated that IAA was the most potent type of auxin for the regeneration of witloof chicory. Another noteworthy observation was that the combination of 0.3 mg l -1 IAA with 0.5 mg l -1 KIN produced nearly four times more shoots per explant than when 0.5 mg l -1 KIN was used alone (18.3 shoots per explant compared to 5.5 shoots, Table 2).…”
Section: Discussionsupporting
confidence: 95%
“…The combinations of NAA with either KIN or BAP produced similar results while the combination of IAA with KIN was significantly more successful than that with BAP in terms of the mean number of shoots produced per explant (18.3 shoots vs. 10.7 shoots, respectively). This finding is consistent with the results of Vermeulen et al (1992) who demonstrated that IAA was the most potent type of auxin for the regeneration of witloof chicory. Another noteworthy observation was that the combination of 0.3 mg l -1 IAA with 0.5 mg l -1 KIN produced nearly four times more shoots per explant than when 0.5 mg l -1 KIN was used alone (18.3 shoots per explant compared to 5.5 shoots, Table 2).…”
Section: Discussionsupporting
confidence: 95%
“…In contrast to the situation for root chicory, appropriate herbicides are available for sugarbeet and chemical weed control in Jerusalem artichoke is not generally necessary. Since resistance to glyphosate and sulfonylurea herbicides has been found in chicory (Sellin et al, 1992; Vermeulen et al, 1992; Lavigne et al, 1994), herbicide‐resistant root chicory cultivars may offer a new herbicide option in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…This vector construct was used to transform leaf discs of Nicotiana tabacum var. Samson NN and Cichorium intybus by Agrobacterium tumefaciens strain LB4044 following published procedures [13,14]. Chicory transformation was carried out at the biotechnology department of Nunhems Zaden, Haelen, The Netherlands.…”
Section: Transformation and Plant Materialsmentioning
confidence: 99%